Blastomycosis outbreak in Escabana, Michigan, United States of America, 2023. - Braidy Sutton; Ashley Quigley (University of New South Wales, 2023)
Blastomycosis is a fungal disease, that though endemic to the state of Michigan, has resulted in a large outbreak of potentially unusual scale and transmission. This outbreak is centred on a paper mill, and is reporting 115 cases, 13 hospitalisations, and 1 death. Current identification of how the fungal spore was transmitted is focussed on the ductwork throughout the mill, which would represent an unusual spore-dispersal and transmission method. Additionally, the size of the outbreak is four times larger than annualised data available from Michigan, indicating that this is an outbreak of interest.